2020
DOI: 10.1002/jpen.1818
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Composition Among Long‐Term Parenteral Nutrition Patients: Postmortem Assessment of Calcium, Phosphorus, Magnesium, and Select Trace Elements

Abstract: Background Patients receiving long‐term parenteral nutrition (PN) treatment are at risk of developing metabolic bone diseases (MBDs). The bone compartment serves as a repository for a range of metal(loid)s that are administered intravenously to patients via PN solutions. Thus, the mineral composition of patient bones may be linked to the development of MBDs in this group. Methods We measured 12 elements in bone samples obtained post mortem from 7 long‐term (2–21 years) PN patients and 18 control bones obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Minerals are one of the six essential nutrients that play a key role in maintaining the body’s metabolism and osmotic pressure balance ( 40 ). Table 7 summarizes the mineral contents of six SDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Minerals are one of the six essential nutrients that play a key role in maintaining the body’s metabolism and osmotic pressure balance ( 40 ). Table 7 summarizes the mineral contents of six SDs.…”
Section: Resultsmentioning
confidence: 99%
“…According to the United States daily recommended sodium intake of 2,400 mg, five tablespoons (one tablespoon is equal to 13 mg) of SD contained between 126.1 and 358.15 mg of Na, which was equal to 5.25–14.92% of the United States daily recommended daily 2,400 mg sodium allowance. Likewise, K is a key element that can aid muscle contraction and can alleviate hypertension caused by a high-Na diet ( 40 ). The K content in SD3 was significantly higher than that of the other groups ( P °<°0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Bone fractures, especially when treated surgically, are associated with changes in the homeostasis of TEs. [ 18 ] Experimental studies have shown that TEs, a part of supplementing nutrition, have a positive effect on the healing of bone fractures. [ 19 ] However, the clinical application of supplementation of TEs in fracture patients to promote fracture healing and the associated molecular mechanisms remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The bone is the main storage site for Ca and Mg ions in the mammalian body. Bone fractures, especially when treated surgically, are associated with changes in the homeostasis of TEs [18] . Experimental studies have shown that TEs, a part of supplementing nutrition, have a positive effect on the healing of bone fractures [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The spray chamber was maintained at 2 C and 20% O 2 in Ar was added. The isotopes monitored were 202 Hg, 196 Hg, and 205 Tl, as IS. The LODs were 0.04 and 0.02 ng mL À1 for MeHg and iHg, respectively, by the ICP-MS method, and 0.12 and 0.14 ng mL À1 for MeHg and iHg, respectively, by the AFS method.…”
Section: Vapour Generation Procedures and Atomic Uorescence Spectrom...mentioning
confidence: 99%